Intimate partner violence during pregnancy and the risk for adverse infant outcomes: a systematic review and meta‐analysis. (9th March 2016) - Donovan, BM; Spracklen, CN; Schweizer, ML; Ryckman, KK; Saftlas, AF
Abstract : Background: Intimate partner violence (IPV) is of particular concern during pregnancy when not one, but two lives are at risk. Previous meta‐analyses have suggested an association between IPV and adverse birth outcomes; however, many large studies have since been published, illustrating the need for updated pooled effect estimates. Objectives: To evaluate the relationship between IPV during pregnancy and the risk of preterm birth (PTB), low‐birthweight (LBW), and small‐for‐gestational‐age (SGA) infants. Search strategy: We searched PubMed and SCOPUS (from inception until May 2015), and the reference lists of the relevant studies. Selection criteria: Observational studies comparing the rates of at least one adverse birth outcome (SGA, LBW, or PTB) in women who experienced IPV during pregnancy and those who did not. Data collection and analysis: Data extracted from 50 studies were pooled and pooled odds ratios were calculated using random‐effects models. Main results: Intimate partner violence (IPV) was significantly associated with PTB (OR 1.91, 95% CI 1.60–2.29) and LBW (OR 2.11, 95% CI 1.68–2.65), although a large level of heterogeneity was present for both ( I 2 = 84 and 91%, respectively). The association with SGA was less pronounced and marginally significant (OR 1.37, 95% CI 1.02–1.84), although fewer studies were available for meta‐analysis ( n = 7). Conclusions: Our meta‐analysis indicates that women who experienced IPV during pregnancy are at increased risk of having a PTB, and an LBW or an SGA infant. More studies examining the association between IPV and SGA are needed. Tweetable Abstract: Meta‐analysis of IPV during pregnancy finds increased risk for preterm birth, LBW and SGA infants. Tweetable Abstract: Meta‐analysis of IPV during pregnancy finds increased risk for preterm birth, LBW and SGA infants.